Bimolecular long-chain alkyl silane gel composition and preparation method thereof

By modifying thermally conductive aluminum powder with a bimolecular long-chain alkylsilane coupling agent, a thermally conductive gel with high thermal conductivity and excellent resistance to humid heat aging was prepared. This solved the problem of performance degradation of aluminum powder-based materials under high temperature and high humidity, achieving better heat dissipation and reliability, and is suitable for heat dissipation of high-power CPUs.

CN120865714APending Publication Date: 2025-10-31DEBANG (KUNSHAN) MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511137625.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing aluminum powder-based thermal conductive gel materials exhibit performance degradation under high temperature and humidity conditions, leading to reliability issues. Furthermore, their poor heat transfer efficiency makes it difficult to meet the heat dissipation requirements of high-power CPUs.

Method used

Thermally conductive aluminum powder was modified with a bimolecular long-chain alkylsilane coupling agent. By controlling the amount and reactivity of thermally conductive fillers of various particle sizes, a thermally conductive gel with high thermal conductivity and excellent resistance to humid heat aging was prepared, thereby reducing the minimum adhesive line thickness and thermal resistance.

Benefits of technology

It improves the heat dissipation effect and resistance to damp heat aging of thermal conductive gel, making it suitable for the heat dissipation needs of high-power CPUs. It is easy to operate and the reaction conditions are mild.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005548622410000031
    Figure BDA0005548622410000031
  • Figure BDA0005548622410000051
    Figure BDA0005548622410000051
  • Figure BDA0005548622410000141
    Figure BDA0005548622410000141
Patent Text Reader

Abstract

The invention belongs to the technical field of organic silicon materials, and particularly relates to a bimolecular long-chain alkyl silane gel composition and a preparation method thereof, the composition comprises vinyl-terminated polydimethylsiloxane, hydrogen-containing polysiloxane, a bimolecular long-chain alkyl silane coupling agent, a heat-conducting filler, a curing inhibitor and a platinum catalyst. The invention also provides a preparation method of the bimolecular long-chain alkylsilane gel composition, the preparation method uses the bimolecular long-chain alkylsilane coupling agent to modify the heat-conducting aluminum powder, and the prepared heat-conducting gel has high heat conductivity and better damp-heat aging resistance. The minimum bonding line thickness (BLT) of the prepared heat-conducting gel composition can be reduced and the thermal resistance can be reduced by controlling the use amount of the heat-conducting fillers with various particle sizes, so that the gel has a better heat dissipation effect and can be used for meeting the heat dissipation requirement of a high-power CPU (Central Processing Unit).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organosilicon materials technology, specifically relating to a bimolecular long-chain alkylsilane gel composition and its preparation method. Background Technology

[0002] As human society moves towards digitalization and artificial intelligence, today's high-performance chips, such as AI training chips (e.g., NVIDIA H100), 5G millimeter-wave RF chips, and autonomous driving computing platform chips, have seen their power density increase from the traditional 5-10Wcm². -2 Soaring to 100Wcm -2 In highly integrated devices, prolonged operation can release and accumulate significant amounts of heat, leading to temperature increases or localized overheating. This, in turn, can reduce the performance, reliability, safety, and lifespan of electronic components.

[0003] To address the heat dissipation problem of electronic components, silicone thermal interface materials are widely used to fill the micro-gaps between components and heat sinks, reducing thermal resistance and improving heat transfer efficiency during the "confined phase" of the heat dissipation process, thus significantly enhancing the overall heat dissipation effect. Aluminum powder-filled silicone thermal interface materials offer advantages such as low bond line thickness (BLT), low contact thermal resistance, no damage to the chip, and low cost. Materials with thermal conductivity greater than 6 W / m² can be prepared by blending aluminum powders of different particle sizes. -1 K -1 Organosilicon thermally conductive gel (TIM-1) is an important heat dissipation material for chip heat dissipation. However, under high temperature and humidity conditions, aluminum powder reacts with water vapor, forming defects and degrading material performance. Reliability has become a pressing problem that needs to be solved for aluminum powder-based TIM-1 materials. Therefore, it is necessary to improve the reliability of aluminum powder-based TIM-1.

[0004] Patent application CN117701234A discloses a thermally conductive silicone composite material for chip packaging and its preparation method. The method involves surface modification of the thermally conductive filler using a T-shaped symmetrical macromolecular alkoxysilane treatment agent, employing brush-like polysiloxane as a crosslinking agent, and adding components such as a tackifier with a specific structure. This results in a thermally conductive silicone composite material with properties including high thermal conductivity, low viscosity, low modulus, high elongation at break, high flexibility, high resilience, low interface thickness, and low thermal resistance. However, the preparation of this T-shaped symmetrical macromolecular alkoxysilane requires the addition of lithium salts, which poses a certain degree of hazard. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a bimolecular long-chain alkylsilane gel composition and its preparation method. The method uses a bimolecular long-chain alkylsilane coupling agent to modify thermally conductive aluminum powder, giving the aluminum powder better resistance to damp heat. This results in a thermally conductive gel with high thermal conductivity and improved resistance to damp heat aging. Controlling the amount of thermally conductive fillers of various particle sizes can reduce the minimum binder line thickness (BLT) of the prepared thermally conductive gel composition, lowering thermal resistance and improving heat dissipation, making it suitable for the heat dissipation needs of high-power CPUs.

[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: a bimolecular long-chain alkylsilane gel composition.

[0007] The composition comprises the following components: vinyl-terminated polydimethylsiloxane, hydrogen-containing polysiloxane, bimolecular long-chain alkylsilane coupling agent, thermally conductive filler, curing inhibitor, and platinum catalyst.

[0008] Furthermore, by mass fraction, the content of each component is as follows: vinyl-terminated polydimethylsiloxane is 2-10 wt%, hydrogen-containing polysiloxane is 0.2-1 wt%, bimolecular long-chain alkylsilane coupling agent is 0.1-0.5 wt%, curing inhibitor is 50-500 ppm, platinum catalyst is 1-5 ppm, and thermally conductive filler is the balance.

[0009] Furthermore, the vinyl-terminated polydimethylsiloxane is at least one of the following specifications with a viscosity range of 100-2000 mPa·s at 25°C.

[0010] Furthermore, the vinyl-terminated polydimethylsiloxane is at least one of the following: a viscosity range of 200-1000 mPa·s at 25°C and a vinyl content of 0.2-0.7 wt%.

[0011] Furthermore, the hydrogen-containing polysiloxane includes a chain extender and a crosslinking agent, wherein the chain extender is a terminal hydrogen silicone oil with silane bonds at both ends of the molecule, and the crosslinking agent is at least one of a side-containing hydrogen silicone oil with silane bonds in the side chain of the molecule and a terminal-side hydrogen silicone oil with silane bonds at both ends of the molecule and in the side chain.

[0012] Furthermore, the viscosity of the terminal hydrogen silicone oil is 5-50 mPa·s, and the hydrogen content in the terminal hydrogen silicone oil is 0.02-0.2 wt%; the viscosity of the side-containing hydrogen silicone oil is 50-1500 mPa·s, and the hydrogen content in the side-containing hydrogen silicone oil is 0.02-0.2 wt%; the viscosity of the terminal-side hydrogen silicone oil is 50-200 mPa·s, and the hydrogen content in the terminal-side hydrogen silicone oil is 0.05-0.2 wt%; wherein the ratio of hydrogen mass content in the chain extender and the crosslinking agent is (2-10):1.

[0013] Furthermore, the thermally conductive filler includes aluminum powder, zinc oxide, and aluminum oxide.

[0014] Furthermore, thermally conductive fillers are classified according to particle size, including large-particle-size thermally conductive fillers, medium-particle-size thermally conductive fillers, and small-particle-size thermally conductive fillers;

[0015] The large-particle-size thermally conductive filler has an average particle size D. 50大 It consists of spherical or near-spherical aluminum powder with a diameter of 10-30 μm.

[0016] The medium-sized thermally conductive filler has an average particle size D. 50中 It consists of spherical or near-spherical alumina with a diameter of 2-5 μm;

[0017] The small-particle-size thermally conductive filler has an average particle size D. 50小 Zinc oxide or aluminum oxide with a thickness of 0.3-1 μm;

[0018] Among the large-particle-size thermally conductive fillers, the maximum particle size D of aluminum powder is... max With average particle size D 50大 The relationship is: D 50大 ≤D max ≤2D 50大 .

[0019] Furthermore, in thermally conductive fillers, the ratio of the total mass of large-particle-size thermally conductive fillers and medium-particle-size thermally conductive fillers to the mass of small-particle-size thermally conductive fillers is 1:(0.1-0.2).

[0020] Furthermore, the curing inhibitor is at least one of ethynylcyclohexanol, tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane, and di[(1,1-dimethyl-2-propynyl)oxy]dimethylsilane.

[0021] Furthermore, the platinum catalyst is a platinum-divinyltetramethyldisiloxane complex diluted with vinyl silicone oil (Castel platinum catalyst).

[0022] Furthermore, the chemical structural formula of the bimolecular long-chain alkylsilane coupling agent is as follows:

[0023]

[0024] Wherein, R is a long-chain alkyl group of C8-C16.

[0025] Furthermore, the bimolecular long-chain alkylsilane coupling agent is preferably a bimolecular decylsilane coupling agent or a bimolecular dodecylsilane coupling agent.

[0026] Furthermore, the mass ratio of the bimolecular long-chain alkylsilane coupling agent to the thermally conductive filler is 1:(200-450).

[0027] Furthermore, the preparation method of the bimolecular long-chain alkylsilane coupling agent includes the following steps:

[0028] S1. Under inert gas, long-chain alkylsilane coupling agent and anhydrous hydrocarbon solvent are mixed evenly to obtain mixed solution 1;

[0029] S2. Under inert gas, the mixed solution 1 from step S1 is added to an anhydrous solvent containing the catalyst to obtain mixed solution 2.

[0030] S3. Under inert gas, tetramethyldihydrodisiloxane is added to the mixed solution 2 in step S2 to carry out a decarbonization condensation reaction.

[0031] S4. Add an adsorbent to remove the catalyst and obtain a bimolecular long-chain alkylsilane coupling agent.

[0032] Furthermore, in step S1, the long-chain alkylsilane coupling agent is at least one of octylsilane coupling agent, decylsilane coupling agent, dodecylsilane coupling agent, and hexadecylsilane coupling agent; the anhydrous hydrocarbon solvent includes at least one of n-hexane, isooctane, toluene, and isodecane; in step S2, the solvent is preferably toluene.

[0033] Furthermore, in step S2, the catalyst is tris(pentafluorophenyl)boron.

[0034] Furthermore, the adsorbent is at least one of neutral alumina and activated carbon.

[0035] Furthermore, in step S1, after mixing evenly, the temperature is kept constant at 0-35℃, wherein the mass ratio of long-chain alkylsilane coupling agent to anhydrous hydrocarbon solvent is 1:(0.5-5).

[0036] In step S2, the molar ratio of the catalyst to the long-chain alkylsilane coupling agent is (0.1-1):100;

[0037] In step S3, the reaction temperature is 25-30℃ and the reaction time is 0.5-5h, wherein the molar ratio of tetramethyldihydrodisiloxane (HMMH) to long-chain alkylsilane coupling agent is (0.1-0.5):1.

[0038] This invention also discloses a method for preparing a bimolecular long-chain alkylsilane gel composition, the preparation method comprising:

[0039] (1) Mix the vinyl-terminated polydimethylsiloxane component and the bimolecular long-chain alkylsilane coupling agent evenly;

[0040] (2) Add thermally conductive filler and mix evenly, then dehydrate under vacuum;

[0041] (3) Add hydrogen-containing polysiloxane, curing inhibitor and platinum catalyst in sequence, and mix well;

[0042] (4) Vacuum degassing, and store at -40-0℃ after filling.

[0043] The beneficial effects of this invention are:

[0044] (1) This invention provides a bimolecular long-chain alkylsilane gel composition and its preparation method. The preparation method uses a bimolecular long-chain alkylsilane coupling agent to modify thermally conductive aluminum powder. By controlling the mass ratio of the bimolecular long-chain alkylsilane coupling agent to the thermally conductive filler, and optimizing the gel preparation process based on the reactivity of the bimolecular long-chain silane coupling agent, the prepared thermally conductive gel exhibits high thermal conductivity and better resistance to damp heat aging. Furthermore, by controlling the amount of thermally conductive fillers of various particle sizes, better interaction between the thermally conductive fillers and the bimolecular long-chain alkylsilane is achieved. Ultimately, while maintaining better resistance to damp heat aging, the minimum adhesion line thickness (BLT) of the prepared thermally conductive gel composition is reduced, lowering thermal resistance and resulting in better heat dissipation. In summary, the obtained gel exhibits further improved thermal conductivity and resistance to damp heat aging, making it suitable for the heat dissipation needs of high-power CPUs.

[0045] (2) The present invention provides a method for preparing a bimolecular long-chain alkylsilane gel composition, wherein the preparation process of the bimolecular long-chain alkylsilane coupling agent has the advantages of simple operation and mild reaction conditions. Detailed Implementation

[0046] The specific embodiments of the present invention will be described in detail below. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used is for describing particular embodiments only and is not intended to limit the invention.

[0048] A bimolecular long-chain alkylsilane gel composition, the composition comprising the following components: vinyl-terminated polydimethylsiloxane, hydrogen-containing polysiloxane, bimolecular long-chain alkylsilane coupling agent, thermally conductive filler, curing inhibitor, and platinum catalyst.

[0049] Specifically, by mass fraction, the content of vinyl-terminated polydimethylsiloxane is 2-10 wt%, the content of hydrogen-containing polysiloxane is 0.2-1 wt%, the content of bimolecular long-chain alkylsilane coupling agent is 0.1-0.5 wt%, the thermally conductive filler is the balance, the content of curing inhibitor is 50-500 ppm, and the content of platinum catalyst is 1-5 ppm.

[0050] Specifically, the vinyl-terminated polydimethylsiloxane is at least one of the following specifications with a viscosity range of 100-2000 mPa·s at 25°C.

[0051] More specifically, the vinyl-terminated polydimethylsiloxane is at least one of the following: a viscosity range of 200-1000 mPa·s at 25°C and a vinyl content of 0.2-0.7 wt%.

[0052] Specifically, the hydrogen-containing polysiloxane includes a chain extender and a crosslinking agent, wherein the chain extender is a terminal hydrogen silicone oil with silane bonds at both ends of the molecule, and the crosslinking agent is at least one of a side-containing hydrogen silicone oil with silane bonds in the side chain of the molecule and a terminal-side hydrogen silicone oil with silane bonds at both ends of the molecule and in the side chain.

[0053] More specifically, the viscosity of the terminal hydrogen silicone oil is 5-50 mPa·s (25°C), and the hydrogen content in the terminal hydrogen silicone oil is 0.02-0.2 wt%; the viscosity of the side-containing hydrogen silicone oil is 50-1500 mPa·s (25°C), and the hydrogen content in the side-containing hydrogen silicone oil is 0.02-0.2 wt%; the viscosity of the terminal-side hydrogen silicone oil is 50-200 mPa·s (25°C), and the hydrogen content in the terminal-side hydrogen silicone oil is 0.05-0.2 wt%; wherein the ratio of hydrogen mass content in the chain extender and the crosslinking agent is (2-10):1.

[0054] Specifically, the thermally conductive filler includes aluminum powder, zinc oxide, and aluminum oxide.

[0055] Specifically, thermally conductive fillers are classified according to particle size into large-particle-size thermally conductive fillers, medium-particle-size thermally conductive fillers, and small-particle-size thermally conductive fillers.

[0056] The large-particle-size thermally conductive filler has an average particle size D. 50大 It consists of spherical or near-spherical aluminum powder with a diameter of 10-30 μm.

[0057] The medium-sized thermally conductive filler has an average particle size D. 50中 It consists of spherical or near-spherical alumina with a diameter of 2-5 μm;

[0058] The small-particle-size thermally conductive filler has an average particle size D. 50小 Zinc oxide or aluminum oxide with a thickness of 0.3-1 μm;

[0059] Among the large-particle-size thermally conductive fillers, the maximum particle size D of aluminum powder is... max With average particle size D 50大 The relationship is: D 50大 ≤D max ≤2D 50大 .

[0060] More specifically, in thermally conductive fillers, the ratio of the total mass of large-particle-size thermally conductive fillers and medium-particle-size thermally conductive fillers to the mass of small-particle-size thermally conductive fillers is 1:(0.1-0.2).

[0061] Specifically, the curing inhibitor is at least one of ethynylcyclohexanol, tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane, and di[(1,1-dimethyl-2-propynyl)oxy]dimethylsilane;

[0062] Specifically, the platinum catalyst is a platinum-divinyltetramethyldisiloxane complex diluted with vinyl silicone oil (Castel platinum catalyst).

[0063] Specifically, the chemical structural formula of the bimolecular long-chain alkylsilane coupling agent is as follows:

[0064]

[0065] Wherein, R is a long-chain alkyl group of C8-C16.

[0066] Specifically, the preferred bimolecular long-chain alkylsilane coupling agents are bimolecular decylsilane coupling agents and bimolecular dodecylsilane coupling agents.

[0067] More specifically, the mass ratio of the bimolecular long-chain alkylsilane coupling agent to the thermally conductive filler is 1:(200-450).

[0068] Specifically, the preparation method of the bimolecular long-chain alkylsilane coupling agent in this embodiment of the invention includes the following steps:

[0069] S1. Under inert gas, long-chain alkylsilane coupling agent and anhydrous hydrocarbon solvent are mixed evenly to obtain mixed solution 1;

[0070] S2. Under inert gas, the mixed solution 1 from step S1 is added to an anhydrous solvent containing the catalyst to obtain mixed solution 2.

[0071] S3. Under inert gas, tetramethyldihydrodisiloxane is added to the mixed solution 2 in step S2 to carry out a decarbonization condensation reaction.

[0072] S4. Add an adsorbent to remove the catalyst and obtain a bimolecular long-chain alkylsilane coupling agent.

[0073] Specifically, in step S1, the long-chain alkylsilane coupling agent is at least one of octylsilane coupling agent, decylsilane coupling agent, dodecylsilane coupling agent, and hexadecylsilane coupling agent; the anhydrous hydrocarbon solvent includes at least one of n-hexane, isooctane, toluene, and isodecane.

[0074] Specifically, the mass ratio of long-chain alkylsilane coupling agent to anhydrous hydrocarbon solvent is 1:(0.5-5).

[0075] More specifically, the specific operation of step S1 is as follows:

[0076] Under nitrogen atmosphere, long-chain alkylsilane coupling agent is mixed with anhydrous hydrocarbon solvent and stirred until homogeneous. The mixture is then kept at a constant temperature of 0-35℃ to obtain mixed solution 1.

[0077] Specifically, in step S2, the molar ratio of the catalyst to the long-chain alkylsilane coupling agent is (0.1-1):100.

[0078] Specifically, in step S2, the catalyst is tris(pentafluorophenyl)boron.

[0079] More specifically, the specific operation of step S2 is as follows:

[0080] Under nitrogen atmosphere, the catalyst is first dissolved in anhydrous toluene, and then the mixed solution 1 from step S1 is added to the anhydrous toluene containing the catalyst and stirred evenly to obtain mixed solution 2.

[0081] Specifically, in step S3, the molar ratio of tetramethyldihydrodisiloxane (HMMH) to the long-chain alkylsilane coupling agent is (0.1-0.5):1.

[0082] More specifically, the specific operation of step S3 is as follows:

[0083] Under nitrogen atmosphere, tetramethyldihydrodisiloxane is added to the mixed solution 2 in step S2 at a rate of 1-20 mL per minute using a peristaltic pump to carry out a decarbonization condensation reaction; methane is released, and after the addition is complete, the temperature is restored to 25-30℃, and the reaction continues for 0.5-5 h.

[0084] Specifically, in step S4, the adsorbent is at least one of neutral alumina and activated carbon.

[0085] More specifically, the specific operation of step S4 is as follows:

[0086] Add adsorbent and stir for 1-12 hours to remove catalyst. Filter to remove adsorbent. Remove solvent and excess unreacted long-chain alkylsilane coupling agent by vacuum distillation to obtain bimolecular long-chain alkylsilane coupling agent.

[0087] A method for preparing a bimolecular long-chain alkylsilane gel composition, the preparation method comprising:

[0088] (1) Mix the vinyl-terminated polydimethylsiloxane component and the bimolecular long-chain alkylsilane coupling agent evenly;

[0089] (2) Add thermally conductive filler and mix evenly, heat and stir evenly, vacuum dehydrate, and cool to 20-30℃;

[0090] (3) Add hydrogen-containing polysiloxane and stir evenly, then add curing inhibitor and stir evenly, and finally add platinum catalyst and mix evenly.

[0091] (4) Vacuum degassing, and store at -40-0℃ after filling.

[0092] The components used in the embodiments and comparative examples of this invention are only for better explanation of the technology of this invention and are not intended to limit the technology of this invention. Except for C1 and C2, which are synthesized in the embodiments of this invention, all other components used in this invention are derived from commercial products. The components used in the embodiments and comparative examples are as follows:

[0093] A1: Vinyl-terminated polydimethylsiloxane with a viscosity of 200 mPa·s (vinyl content 0.68 wt%, Kawana Chemical HV200).

[0094] A2: Vinyl-terminated polydimethylsiloxane with a viscosity of 500 mPa·s (vinyl content 0.43 wt%, Kawana Chemical HV500).

[0095] A3: Vinyl-terminated polydimethylsiloxane with a viscosity of 1000 mPa·s (vinyl content 0.32 wt%, Kawana Chemical HV1000).

[0096] B1: Hydrogen-terminated polydimethylsiloxane (viscosity 15 mPa.s, H content 0.13 wt%, Haiduo Silicon Material, HHD-14).

[0097] B2: Side-containing hydrogen polydimethylsiloxane (viscosity 500 mPa.s, H content 0.11 wt%, Evonik Chemicals, Crosslinker 120).

[0098] B3: Hydrogen-containing polydimethylsiloxane (viscosity 120 mPa.s, H content 0.10 wt%, Haiduo Silicon Material, DTH-010t).

[0099] C1: Bimolecular decyltrimethoxysilane (the product synthesized in Example 1 of this invention).

[0100] C2: Dimolecular dodecyltrimethoxysilane (the product synthesized in Example 2 of this invention).

[0101] D1: Average particle size D 50小 Single-crystal alumina with a diameter of 0.5 μm (Sumitomo Chemical, AA04).

[0102] D2: Average particle size D 50小 0.6μm rod-shaped zinc oxide (Jiangsu Zhenzhong Zinc Industry).

[0103] D3: Average particle size D 50中 It is a 3μm nitrogen-atomized spherical aluminum powder (Yuanyang Aluminum).

[0104] D4: Average particle size D 50中 It is a 5μm nitrogen-atomized spherical aluminum powder (Yuanyang Aluminum).

[0105] D5: Average particle size D 50大 It is 12μm, D max The aluminum powder is a near-spherical powder with a diameter of 24μm (Ocean Aluminum).

[0106] D6: Average particle size D 50大 20μm, D max The aluminum powder is a spherical powder with a diameter of 40μm (Yuanyang Aluminum).

[0107] E1: 1-Ethynylcyclohexanol (Cas No. 78-27-3, Aladdin Reagent).

[0108] E2: Di[(1,1-dimethyl-2-propynyl)oxy]dimethylsilane (Cas No. 53863-99-3, Aladdin Reagent).

[0109] E3: Tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane (Cas No. 83817-71-4, Aladdin reagent).

[0110] F: Karstedt platinum catalyst (Heraeus, Karstedt Catalyst, Pt = 5000ppm, Guizhou Guoyan Platinum Industry).

[0111] Example 1

[0112] The preparation steps for a bimolecular decyltrimethoxysilane coupling agent are as follows:

[0113] S1. Under nitrogen atmosphere, 262.5 g (1 mol) of decyltrimethoxysilane and 172 g (2 mol) of anhydrous n-hexane were mixed and stirred until homogeneous, and then kept at a constant temperature of 25 °C to obtain mixed solution 1.

[0114] S2. Under nitrogen conditions, 0.512 g (1 mmol) of tris(pentafluorophenyl)borane was first dissolved in 10.0 mL of anhydrous toluene. Then, the mixed solution 1 from step S1 was added to the anhydrous toluene containing the catalyst and stirred until homogeneous to obtain mixed solution 2.

[0115] Under nitrogen conditions, 67 g (0.5 mol) of tetramethyldihydrodisiloxane was added to the mixed solution 2 in step S2 at a rate of 1 mL per minute using a peristaltic pump to carry out a decarbonization condensation reaction; methane was released, and after the addition was complete, the temperature was raised to 25 °C and the reaction continued for 5 h.

[0116] S4. Add 25g of neutral alumina and stir to adsorb for 1h to remove the catalyst. Filter to remove the neutral alumina. Remove the solvent and unreacted small molecules by vacuum distillation to obtain 276.5g of bimolecular decyltrimethoxysilane coupling agent with a purity of 97.5%.

[0117] Example 1 describes the preparation of a bimolecular long-chain alkylsilane gel composition. The specific components of the composition are as follows:

[0118] Vinyl-terminated polydimethylsiloxane is A1: vinyl-terminated polydimethylsiloxane with a viscosity of 200 mPa·s (vinyl content 0.68 wt%) and A3: vinyl-terminated polydimethylsiloxane with a viscosity of 1000 mPa·s (vinyl content 0.32 wt%).

[0119] The hydrogen-containing polysiloxanes are B1: end-hydrogen-containing polydimethylsiloxane (viscosity 15 mPa.s, H content 0.13 wt%) and B3: end-side hydrogen-containing polydimethylsiloxane (viscosity 120 mPa.s, H content 0.10 wt%).

[0120] The bimolecular long-chain alkylsilane coupling agent is the C1: bimolecular decyltrimethoxysilane coupling agent synthesized in Example 1 of this invention.

[0121] The thermally conductive filler is D1: average particle size D 50小 Single-crystal alumina with a particle size of 0.5 μm, D3: average particle size D 50中 3μm nitrogen-atomized spherical aluminum powder and D5: average particle size D 50大 It is 12μm, D max It is a spherical aluminum powder with a diameter of 24 μm.

[0122] The curing inhibitor is E1: 1-ethynylcyclohexanol.

[0123] The platinum catalyst is F: Heraeus, Karstedt Catalyst (Pt = 5000 ppm).

[0124] The preparation steps for a bimolecular long-chain alkylsilane gel composition are as follows:

[0125] (1) Mix 6.0g A1, 6.0g A3 and 0.25g C1 thoroughly;

[0126] (2) Add 16.0g D1, 32.0g D3 and 58g D5 thermally conductive fillers and mix evenly. Heat to 60℃ and stir for 1h. Then heat to 100℃ and vacuum dehydrate for 0.5h. Cool to 25℃.

[0127] (3) Add 0.8g B1 and 0.45g B3 of hydrogen-containing polysiloxane and stir for 0.5h, then add 0.012g E1 of curing inhibitor and stir for 0.5h, and finally add 0.05g F of platinum catalyst and mix for 0.5h;

[0128] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0129] Example 2

[0130] The preparation steps for a bimolecular dodecyltrimethoxysilane coupling agent are as follows:

[0131] S1. Under nitrogen atmosphere, 1162 g (4 mol) of dodecyltrimethoxysilane and 921.4 g (10 mol) of anhydrous toluene were mixed and stirred until homogeneous, and then kept at a constant temperature of 5 °C to obtain mixed solution 1.

[0132] S2. Under nitrogen conditions, 20.48 g (40 mmol) of tris(pentafluorophenyl)borane was first dissolved in 200 mL of anhydrous toluene. Then, the mixed solution 1 from step S1 was added to the anhydrous toluene containing the catalyst and stirred until homogeneous to obtain mixed solution 2.

[0133] Under nitrogen conditions, 134 g (2 mol) of tetramethyldihydrodisiloxane was added to the mixed solution 2 in step S2 at a rate of 5 mL per minute using a peristaltic pump to carry out a decarbonization condensation reaction; methane was released, and after the addition was complete, the temperature was returned to 25 °C and the reaction continued for 1 h.

[0134] S4. Add 200g of activated carbon and stir for 6h to remove the catalyst. Filter to remove the activated carbon. Remove the solvent and unreacted small molecules by vacuum distillation to obtain 606g of bimolecular dodecyltrimethoxysilane coupling agent with a purity of 98.2%.

[0135] Example 2 describes the preparation of a bimolecular long-chain alkylsilane gel composition. The specific components of the composition are as follows:

[0136] Vinyl-terminated polydimethylsiloxane is A2: vinyl-terminated polydimethylsiloxane with a viscosity of 500 mPa·s (vinyl content 0.43 wt%).

[0137] The hydrogen-containing polysiloxanes are B1: end-hydrogen-containing polydimethylsiloxane (viscosity 15 mPa.s, H content 0.13 wt%) and B3: end-side hydrogen-containing polydimethylsiloxane (viscosity 120 mPa.s, H content 0.10 wt%).

[0138] The bimolecular long-chain alkylsilane coupling agent is the C2: bimolecular dodecyltrimethoxysilane coupling agent synthesized in Example 2 of this study.

[0139] The thermally conductive filler is D1: average particle size D 50小 Single-crystal alumina with a particle size of 0.5 μm, D3: average particle size D 50中 3μm nitrogen-atomized spherical aluminum powder and D5: average particle size D 50大 It is 12μm, D max It is a spherical aluminum powder with a diameter of 24 μm.

[0140] The curing inhibitor is E2: bis[(1,1-dimethyl-2-propynyl)oxy]dimethylsilane (Cas No. 53863-99-3).

[0141] The platinum catalyst is F: Heraeus, Karstedt Catalyst (Pt = 5000 ppm).

[0142] The preparation steps for a bimolecular long-chain alkylsilane gel composition are as follows:

[0143] (1) Mix 12g A2 and 0.30g C2 thoroughly;

[0144] (2) Add 16.0g D1, 32.0g D3 and 54g D5 thermally conductive fillers and mix evenly. Heat to 50℃ and stir for 1 hour. Then heat to 100℃ and dehydrate under vacuum for 1 hour. Cool down to 25℃.

[0145] (3) Add 0.8g B1 and 0.30g B3 of hydrogen-containing polysiloxane and stir for 0.5h, then add 0.05g E2 of curing inhibitor and stir for 0.5h, and finally add 0.04g F of platinum catalyst and mix for 0.5h;

[0146] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0147] Example 3

[0148] The preparation of a bimolecular decyltrimethoxysilane coupling agent follows the same steps as in Example 1.

[0149] Example 3 describes the preparation of a bimolecular long-chain alkylsilane gel composition. The specific components of the composition are as follows:

[0150] Vinyl-terminated polydimethylsiloxane is A2: vinyl-terminated polydimethylsiloxane with a viscosity of 500 mPa·s (vinyl content 0.43 wt%) and A3: vinyl-terminated polydimethylsiloxane with a viscosity of 1000 mPa·s (vinyl content 0.32 wt%).

[0151] The hydrogen-containing polysiloxanes are B1: end-hydrogen-containing polydimethylsiloxane (viscosity 15 mPa.s, H content 0.13 wt%) and B3: end-side hydrogen-containing polydimethylsiloxane (viscosity 120 mPa.s, H content 0.10 wt%).

[0152] The bimolecular long-chain alkylsilane coupling agent is the C1: bimolecular decyltrimethoxysilane coupling agent synthesized in Example 1.

[0153] Thermally conductive filler is D2: average particle size D 50小 It is 0.6μm rod-shaped zinc oxide, D3: average particle size D 50中 3μm nitrogen-atomized spherical aluminum powder and D5: average particle size D 50大 It is 12μm, D max It is a spherical aluminum powder with a diameter of 24 μm.

[0154] The curing inhibitor is E3: tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane (Cas No. 83817-71-4).

[0155] The platinum catalyst is F: Heraeus, Karstedt Catalyst (Pt = 5000 ppm).

[0156] The preparation steps for a bimolecular long-chain alkylsilane gel composition are as follows:

[0157] (1) Mix 4g A2, 8g A3 and 0.35g C1 evenly;

[0158] (2) Add 10.0g D2, 35.0g D3 and 60g D5 thermally conductive fillers and mix evenly. Heat to 70℃ and stir for 1h. Then heat to 120℃ and vacuum dehydrate for 0.5h. Cool to 25℃.

[0159] (3) Add 0.7g B1 and 0.20g B3 containing hydrogen polysiloxane and stir for 0.5h, then add 0.05g E3 curing inhibitor and stir for 0.5h, and finally add 0.04g F platinum catalyst and mix for 0.5h;

[0160] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0161] Example 4

[0162] The preparation steps of a bimolecular dodecyltrimethoxysilane coupling agent are the same as those in Example 2.

[0163] Example 4 describes the preparation of a bimolecular long-chain alkylsilane gel composition. The specific components of the composition are as follows:

[0164] The vinyl-terminated polydimethylsiloxane is A1: vinyl-terminated polydimethylsiloxane with a viscosity of 200 mPa·s (vinyl content 0.68 wt%) and A2: vinyl-terminated polydimethylsiloxane with a viscosity of 500 mPa·s (vinyl content 0.43 wt%).

[0165] The hydrogen-containing polysiloxanes are B1: end-hydrogen-containing polydimethylsiloxane (viscosity 15 mPa.s, H content 0.13 wt%) and B2: side-hydrogen-containing polydimethylsiloxane (viscosity 500 mPa.s, H content 0.11 wt%).

[0166] The bimolecular long-chain alkylsilane coupling agent is the C2: bimolecular dodecyltrimethoxysilane coupling agent synthesized in Example 2.

[0167] Thermally conductive filler is D2: average particle size D 50小 0.6μm rod-shaped zinc oxide, D4: average particle size D 50中 5μm nitrogen-atomized spherical aluminum powder and D6: average particle size D 50大 20μm, D max It is a spherical aluminum powder with a diameter of 40 μm.

[0168] The curing inhibitor is E3: tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane (Cas No. 83817-71-4).

[0169] The platinum catalyst is F: Heraeus, Karstedt Catalyst (Pt = 5000 ppm).

[0170] The preparation steps for a bimolecular long-chain alkylsilane gel composition are as follows:

[0171] (1) Mix 8g A1, 4g A2 and 0.5g C2 evenly;

[0172] (2) Add 20.0g D2, 40.0g D4 and 80g D6 thermally conductive fillers and mix evenly. Heat to 80℃ and stir for 1h. Then heat to 120℃ and vacuum dehydrate for 0.5h. Cool down to 25℃.

[0173] (3) Add 0.9g B1 and 0.30g B2 of hydrogen-containing polysiloxane and stir for 0.5h, then add 0.05g E3 of curing inhibitor and stir for 0.5h, and finally add 0.04g F of platinum catalyst and mix for 0.5h;

[0174] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0175] Example 5

[0176] The preparation steps of a bimolecular dodecyltrimethoxysilane coupling agent are the same as those in Example 2.

[0177] Example 5 describes the preparation of a bimolecular long-chain alkylsilane gel composition. The specific components of the composition are as follows:

[0178] The vinyl-terminated polydimethylsiloxane is A1: vinyl-terminated polydimethylsiloxane with a viscosity of 200 mPa·s (vinyl content 0.68 wt%).

[0179] The hydrogen-containing polysiloxanes are B1: end-hydrogen-containing polydimethylsiloxane (viscosity 15 mPa.s, H content 0.13 wt%) and B2: side-hydrogen-containing polydimethylsiloxane (viscosity 500 mPa.s, H content 0.11 wt%).

[0180] The bimolecular long-chain alkylsilane coupling agent is the C2: bimolecular dodecyltrimethoxysilane coupling agent synthesized in Example 2.

[0181] The thermally conductive filler is D1: average particle size D 50小 Single-crystal alumina with a particle size of 0.5 μm, D4: average particle size D 50中 5μm nitrogen-atomized spherical aluminum powder and D6: average particle size D 50大 20μm, D max It is a spherical aluminum powder with a diameter of 40 μm.

[0182] The curing inhibitor is E3: tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane (Cas No. 83817-71-4).

[0183] The platinum catalyst is F: Heraeus, Karstedt Catalyst (Pt = 5000 ppm).

[0184] The preparation steps for a bimolecular long-chain alkylsilane gel composition are as follows:

[0185] (1) Mix 12g A1 and 0.6g C2 thoroughly;

[0186] (2) Add 25.0g D1, 45.0g D4 and 85g D6 thermally conductive fillers and mix evenly. Heat to 80℃ and stir for 1 hour. Then heat to 120℃ and dehydrate under vacuum for 0.5 hours. Cool down to 25℃.

[0187] (3) Add 1g B1 and 0.40g B2 of hydrogen-containing polysiloxane and stir for 0.5h, then add 0.05g E3 of curing inhibitor and stir for 0.5h, and finally add 0.04g F of platinum catalyst and mix for 0.5h;

[0188] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0189] Example 6

[0190] The preparation steps of a bimolecular dodecyltrimethoxysilane coupling agent are the same as those in Example 2.

[0191] Example 6 describes the preparation of a bimolecular long-chain alkylsilane gel composition. The composition has the same components as in Example 5, except that:

[0192] Vinyl-terminated polydimethylsiloxane is A1: vinyl-terminated polydimethylsiloxane with a viscosity of 200 mPa·s (vinyl content 0.68 wt%) and A3: vinyl-terminated polydimethylsiloxane with a viscosity of 1000 mPa·s (vinyl content 0.32 wt%).

[0193] The preparation steps for a bimolecular long-chain alkylsilane gel composition are as follows:

[0194] (1) Mix 10g A1, 2g A3 and 0.7g C2 evenly;

[0195] (2) Add 24.0g D1, 45.0g D4 and 80g D6 thermally conductive fillers and mix evenly. Heat to 80℃ and stir for 1h. Then heat to 120℃ and vacuum dehydrate for 0.5h. Cool to 25℃.

[0196] (3) Add 1.2g B1 and 0.25g B2 of hydrogen-containing polysiloxane and stir for 0.5h, then add 0.05g E3 of curing inhibitor and stir for 0.5h, and finally add 0.04g F of platinum catalyst and mix for 0.5h;

[0197] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0198] Comparative Example 1

[0199] Comparative Example 1 prepared a silane gel composition with the same components as in Example 3, except that decyltrimethoxysilane was used instead of the bimolecular decyltrimethoxysilane coupling agent in Comparative Example 1.

[0200] A silane gel composition was prepared using the same steps as in Example 3, except that the specific preparation steps are as follows: In the thermally conductive filler, the ratio of the total mass of the large-particle-size thermally conductive filler and the medium-particle-size thermally conductive filler to the mass of the small-particle-size thermally conductive filler is 1:0.24, which is not within the range of 1:(0.1-0.2). The specific preparation steps are as follows:

[0201] (1) Mix 4g A2, 8g A3 and 0.35g decyltrimethoxysilane evenly;

[0202] (2) Add 20.0g D2, 25.0g D3 and 60g D5 thermally conductive fillers and mix evenly. Heat to 70℃ and stir for 1h. Then heat to 120℃ and vacuum dehydrate for 0.5h. Cool to 25℃.

[0203] (3) Add 0.7g B1 and 0.20g B3 containing hydrogen polysiloxane and stir for 0.5h, then add 0.05g E3 curing inhibitor and stir for 0.5h, and finally add 0.04g F platinum catalyst and mix for 0.5h;

[0204] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0205] Comparative Example 2

[0206] Comparative Example 2 prepared a silane gel composition with the same components as in Example 6, except that dodecyltrimethoxysilane was used instead of the bimolecular dodecyltrimethoxysilane coupling agent in Comparative Example 2.

[0207] The preparation method of a silane gel composition follows the same steps as in Example 6, except that the specific preparation steps are as follows: In the thermally conductive filler, the ratio of the total mass of large-particle-size thermally conductive filler and medium-particle-size thermally conductive filler to the mass of small-particle-size thermally conductive filler is 1:0.30, which is not within the range of 1:(0.1-0.2). The specific preparation steps are as follows:

[0208] (1) Mix 10g A1, 2g A3 and 0.7g dodecyltrimethoxysilane evenly;

[0209] (2) Add 34.0g D1, 35.0g D4 and 80g D6 thermally conductive fillers and mix evenly. Heat to 80℃ and stir for 1h. Then heat to 120℃ and vacuum dehydrate for 0.5h. Cool to 25℃.

[0210] (3) Add 1.2g B1 and 0.25g B2 of hydrogen-containing polysiloxane and stir for 0.5h, then add 0.05g E3 of curing inhibitor and stir for 0.5h, and finally add 0.04g F of platinum catalyst and mix for 0.5h;

[0211] (4) Vacuum degassing for 5 min yields a bimolecular long-chain alkylsilane gel composition, which is then filled and stored at -40-0℃.

[0212] Comparative Example 3

[0213] Comparative Example 3 prepared a silane gel composition with the same components as in Example 3, except that decyltrimethoxysilane was used instead of the bimolecular decyltrimethoxysilane coupling agent in Comparative Example 3.

[0214] A silane gel composition was prepared using the same steps as in Example 3.

[0215] Comparative Example 4

[0216] Comparative Example 4 prepared a silane gel composition with the same components as in Example 6, except that dodecyltrimethoxysilane was used instead of the bimolecular dodecyltrimethoxysilane coupling agent in Comparative Example 4.

[0217] A silane gel composition was prepared using the same steps as in Example 6.

[0218] Comparative Example 5

[0219] Comparative Example 5 prepared a bimolecular long-chain alkylsilane gel composition. The composition and preparation steps were the same as in Example 1, except that the mass of the added component, bimolecular decyltrimethoxysilane, was 0.6. At this time, the mass ratio of bimolecular decyltrimethoxysilane to thermally conductive filler was 1:176.7, which was not within the range of 1:(200-450).

[0220] Comparative Example 6

[0221] Comparative Example 6 prepared a bimolecular long-chain alkylsilane gel composition. The composition and preparation steps were the same as those in Example 1, except that the mass of the added component, bimolecular decyltrimethoxysilane, was 0.2. At this time, the mass ratio of bimolecular decyltrimethoxysilane to thermally conductive filler was 1:530, which was not within the range of 1:(200-450).

[0222] Comparative Example 7

[0223] Comparative Example 7 prepared a bimolecular long-chain alkylsilane gel composition. The composition and preparation steps were the same as in Example 3, except that 20.0g of thermally conductive filler, 25.0g of D3 and 60g of D5 were added to this comparative example. At this time, the ratio of the total mass of the large-particle-size thermally conductive filler and the medium-particle-size thermally conductive filler to the mass of the small-particle-size thermally conductive filler was 1:0.24, which is not within the range of 1:(0.1-0.2).

[0224] In the preparation of the gel composition, the amounts of each component in the embodiments and comparative examples of the present invention are shown in Tables 1 and 2.

[0225] Table 1. Dosage of each component in the gel composition of the examples.

[0226]

[0227] Table 2. Dosage of each component in the comparative gel compositions

[0228]

[0229]

[0230] The tests involved in the preparation of the bimolecular long-chain alkylsilane gel compositions in the embodiments and comparative examples of this invention are as follows:

[0231] Viscosity test: The viscosity was measured at 5 r using an Anton Paar rheometer (Anton Paar MCR302e) with a PP25 rotor.

[0232] Thermal conductivity: Tested according to ISO 22007-2 standard using a HOTDISK thermal conductivity meter. Thermal conductivity was tested at 120mW for 4 seconds with a 6mm thick heatsink.

[0233] Thermal resistance test: Tested according to ASTM D5470 standard using a Taiwan Ruiling LW 9389 thermal resistance meter. Test conditions: temperature 80℃, pressure 40psi.

[0234] Elongation at break test: The prepared single-component thermally conductive silicone gel was extruded onto a fluorinated release film with a 2 mm gap in the middle of the release film. It was cured at 125℃ for 60 min using a flat vulcanizer, and then the elongation at break was tested according to GB / T 528 standard.

[0235] Hardness test: A 6mm thermally conductive sheet was prepared by curing at 125℃ for 60min using a flat vulcanizing apparatus. The average hardness was measured three times using an automatic Shore 00 hardness tester.

[0236] Aging resistance test: Stretch sheets were prepared by curing and cutting according to the requirements of the elongation at break test standard. The stretch sheets were then aged in a uHAST aging chamber at 130°C, 85% RH, and 230 kPa for 192 hours, and the samples were then removed to test the elongation at break. Alternatively, the stretch sheets were aged in a high-temperature aging chamber at 150°C for 120 hours, and the samples were then removed to test the elongation at break. The performance test data of the gel compositions prepared in the embodiments and comparative examples of this invention are shown in Table 3.

[0237] Table 3. Performance test data of the gel compositions prepared in the examples and comparative examples.

[0238]

[0239] As shown in Tables 1 and 3, the bimolecular long-chain alkylsilane gel compositions prepared by the method described in this invention in Examples 1-6 exhibit low thermal resistance. Furthermore, after 192 hours of high-acceleration temperature and humidity stress testing in a uHAST aging chamber at 130°C, 85% RH, and 230 kPa, they also show good elongation after 120 hours of high-temperature aging testing in a 150°C high-temperature aging chamber. This indicates that the thermally conductive gel prepared by this invention has good resistance to damp heat aging and can meet the requirements for high-power CPU heat dissipation.

[0240] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 1 and Example 3 shows that: Comparative Example 1 used decyltrimethoxysilane instead of the bimolecular decyltrimethoxysilane coupling agent. Furthermore, in the thermally conductive filler, the ratio of the total mass of the large-particle-size thermally conductive filler to the total mass of the medium-particle-size thermally conductive filler to the mass of the small-particle-size thermally conductive filler was 1:0.24, which is outside the range of 1:(0.1-0.2). The resulting gel composition showed a significant decrease in elongation at break after high-temperature and high-humidity aging. This is because decyltrimethoxysilane has only one site for reaction with the thermally conductive powder due to steric hindrance. The bimolecular decyltrimethoxysilane coupling agent prepared in this invention has two sites that can react with the thermally conductive powder, significantly improving its resistance to damp heat. Excessive addition of small-particle-size thermally conductive powder makes it difficult to disperse evenly and perfectly fill the gaps in the large-particle-size thermally conductive powder, forming microscopic defects and resulting in a significant decrease in performance after aging.

[0241] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 2 and Example 6 shows that: Comparative Example 2 used dodecyltrimethoxysilane instead of the bimolecular dodecyltrimethoxysilane coupling agent. Furthermore, in the thermally conductive filler, the ratio of the total mass of the large-particle-size thermally conductive filler to the total mass of the medium-particle-size thermally conductive filler to the mass of the small-particle-size thermally conductive filler was 1:0.30, which is outside the range of 1:(0.1-0.2). The resulting gel composition showed a significant decrease in elongation at break after high-temperature and high-humidity aging. This is because excessive small-particle-size filler makes uniform dispersion difficult, resulting in high gel viscosity. Additionally, the resistance to moisture and humid heat erosion after dodecyltrimethoxysilane modification was not as good as that of the bimolecular dodecyltrimethoxysilane coupling agent.

[0242] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 3 and Example 3 shows that when Comparative Example 3 uses decyltrimethoxysilane instead of the bimolecular decyltrimethoxysilane coupling agent, the elongation at break of the final gel composition after high temperature and high humidity aging is significantly reduced. This is because the resistance of the decyltrimethoxysilane-modified powder to water vapor and humid heat erosion is not as good as that of the bimolecular decyltrimethoxysilane coupling agent.

[0243] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 4 and Example 6 shows that when Comparative Example 4 uses dodecyltrimethoxysilane instead of the bimolecular dodecyltrimethoxysilane coupling agent, the elongation at break of the final gel composition after high temperature and high humidity aging is significantly reduced. This is because the resistance of the dodecyltrimethoxysilane-modified powder to water vapor and humid heat erosion is not as good as that of the bimolecular dodecyltrimethoxysilane coupling agent.

[0244] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 5 and Example 1 shows that: Comparative Example 5 prepared a bimolecular long-chain alkylsilane gel composition. When the mass of the added component, bimolecular decyltrimethoxysilane, was 0.6, the viscosity was low, and the elongation at break remained good after aging at 130°C for 192 hours in a uHAST aging chamber at 85% RH and 230 kPa. However, the elongation at break decreased after aging at 150°C for 120 hours. This is because the amount of bimolecular decyltrimethoxysilane was too high. The mass ratio of bimolecular decyltrimethoxysilane to thermally conductive filler was 1:176.7, which is outside the range of 1:(200-450), indicating an excess. After aging at 150°C, the excess coupling agent volatilized, forming defects and resulting in poor high-temperature aging performance.

[0245] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 6 and Example 1 shows that: In Comparative Example 6, a bimolecular long-chain alkylsilane gel composition was prepared. When the mass of the added component, bimolecular decyltrimethoxysilane, was 0.2, the viscosity increased, and the elongation at break after high-temperature and high-humidity aging decreased. This is because when the mass ratio of bimolecular decyltrimethoxysilane to thermally conductive filler is 1:530, which is outside the range of 1:(200-450), the amount of bimolecular decyltrimethoxysilane used is too low, resulting in insufficient surface improvement of the thermally conductive filler and a decrease in high-temperature and high-humidity aging performance.

[0246] Based on the data in Tables 1-3, a comparison of the experimental results of Comparative Example 7 and Example 3 shows that: In preparing a bimolecular long-chain alkylsilane gel composition, this comparative example introduced the bimolecular decyltrimethoxysilane coupling agent described in this invention. At the same time, the ratio of the total mass of large-particle thermally conductive filler and medium-particle thermally conductive filler to the mass of small-particle thermally conductive filler was controlled at 1:0.24, which is not within the range of 1:(0.1-0.2). As a result, the elongation at break increased, and the gel viscosity increased. After high-temperature and high-humidity aging with uHAST, it could still maintain a certain elongation at break, but the thermal resistance was relatively high. This is because the thermally conductive gel modified with a bimolecular decyltrimethoxysilane coupling agent can maintain a certain elongation at break after UHAST high-temperature and high-humidity aging. However, when the ratio of the total mass of large-particle-size thermally conductive filler to the mass of small-particle-size thermally conductive filler is 1:0.24, the excessive amount of small-particle-size thermally conductive filler leads to uneven dispersion, high gel viscosity, and difficulty in fully filling the gaps between large-particle-size thermally conductive powder, resulting in microscopic defects, decreased thermal conductivity, and higher thermal resistance. This indicates that introducing a bimolecular decyltrimethoxysilane coupling agent in a suitable ratio during the preparation of the gel composition can improve the aging performance of the material under high-temperature and high-humidity conditions. However, when the amounts of large-particle-size, medium-particle-size, and small-particle-size thermally conductive fillers are outside the verified range, the bimolecular decyltrimethoxysilane coupling agent and the thermally conductive filler cannot work synergistically, leading to increased thermal resistance in the final gel composition and affecting the thermal conductivity.

[0247] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0248] For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A bimolecular long-chain alkylsilane gel composition, characterized in that, The composition comprises the following components: vinyl-terminated polydimethylsiloxane, hydrogen-containing polysiloxane, bimolecular long-chain alkylsilane coupling agent, thermally conductive filler, curing inhibitor, and platinum catalyst. The components, by mass fraction, are as follows: vinyl-terminated polydimethylsiloxane 2-10 wt%, hydrogen-containing polysiloxane 0.2-1 wt%, bimolecular long-chain alkylsilane coupling agent 0.1-0.5 wt%, curing inhibitor 50-500 ppm, platinum catalyst 1-5 ppm, and thermally conductive filler as the balance.

2. The bimolecular long-chain alkylsilane gel composition according to claim 1, characterized in that, The vinyl-terminated polydimethylsiloxane is at least one of the following specifications with a viscosity range of 100-2000 mPa·s at 25°C; The hydrogen-containing polysiloxane includes a chain extender and a crosslinking agent, wherein the chain extender is a terminal hydrogen silicone oil with silane bonds at both ends of the molecule, and the crosslinking agent is at least one of a side hydrogen silicone oil with silane bonds in the side chain of the molecule and a terminal side hydrogen silicone oil with silane bonds at both ends of the molecule and in the side chain. The thermally conductive filler includes: aluminum powder, zinc oxide, and aluminum oxide; The curing inhibitor is at least one of ethynylcyclohexanol, tris[(1,1-dimethyl-2-propynyl)oxy]methylsilane, and di[(1,1-dimethyl-2-propynyl)oxy]dimethylsilane; The platinum catalyst is a platinum-divinyltetramethyldisiloxane complex diluted with vinyl silicone oil.

3. The bimolecular long-chain alkylsilane gel composition according to claim 2, characterized in that, The vinyl-terminated polydimethylsiloxane is at least one of the following: a viscosity range of 200-1000 mPa·s at 25°C and a vinyl content of 0.2-0.7 wt%. The viscosity of the terminal hydrogen silicone oil is 5-50 mPa·s, and the hydrogen content in the terminal hydrogen silicone oil is 0.02-0.2 wt%; the viscosity of the side-containing hydrogen silicone oil is 50-1500 mPa·s, and the hydrogen content in the side-containing hydrogen silicone oil is 0.02-0.2 wt%; the viscosity of the terminal-side hydrogen silicone oil is 50-200 mPa·s, and the hydrogen content in the terminal-side hydrogen silicone oil is 0.05-0.2 wt%. The ratio of hydrogen mass content in the chain extender and the crosslinking agent is (2-10):

1.

4. The bimolecular long-chain alkylsilane gel composition according to claim 2, characterized in that, Thermally conductive fillers include large-particle-size thermally conductive fillers, medium-particle-size thermally conductive fillers, and small-particle-size thermally conductive fillers; The large-particle-size thermally conductive filler has an average particle size D. 50大 It consists of spherical or near-spherical aluminum powder with a diameter of 10-30 μm. The medium-sized thermally conductive filler has an average particle size D. 50中 It consists of spherical or near-spherical alumina with a diameter of 2-5 μm; The small-particle-size thermally conductive filler has an average particle size D. 50小 Zinc oxide or aluminum oxide with a thickness of 0.3-1 μm; Among the large-particle-size thermally conductive fillers, the maximum particle size D of aluminum powder is... max With average particle size D 50大 The relationship is: D 50大 ≤D max ≤2D 50大 .

5. The bimolecular long-chain alkylsilane gel composition according to claim 4, characterized in that, In thermally conductive fillers, the ratio of the total mass of large-particle-size thermally conductive fillers and medium-particle-size thermally conductive fillers to the mass of small-particle-size thermally conductive fillers is 1:(0.1-0.2).

6. The bimolecular long-chain alkylsilane gel composition according to claim 1, characterized in that, The chemical structural formula of the bimolecular coupling long-chain alkylsilane coupling agent is as follows: Wherein, R is a long-chain alkyl group of C8-C16.

7. The bimolecular long-chain alkylsilane gel composition according to claim 1, characterized in that, The mass ratio of bimolecular long-chain alkylsilane coupling agent to thermally conductive filler is 1:(200-450).

8. A bimolecular long-chain alkylsilane gel composition according to any one of claims 1-7, characterized in that, The preparation method of the bimolecular long-chain alkylsilane coupling agent includes the following steps: S1. Under inert gas, long-chain alkylsilane coupling agent and anhydrous hydrocarbon solvent are mixed evenly to obtain mixed solution 1; S2. Under inert gas, the mixed solution 1 from step S1 is added to an anhydrous solvent containing the catalyst to obtain mixed solution 2. S3. Under inert gas, tetramethyldihydrodisiloxane is added to the mixed solution 2 in step S2 to carry out a decarbonization condensation reaction. S4. Add an adsorbent to remove the catalyst and obtain a bimolecular long-chain alkylsilane coupling agent.

9. The bimolecular long-chain alkylsilane gel composition according to claim 8, characterized in that, In step S1, after mixing evenly, the temperature is kept constant at 0-35℃, wherein the mass ratio of long-chain alkylsilane coupling agent to anhydrous hydrocarbon solvent is 1:(0.5-5); In step S2, the molar ratio of the catalyst to the long-chain alkylsilane coupling agent is (0.1-1):100; In step S3, the reaction temperature is 25-30℃ and the reaction time is 0.5-5h, wherein the molar ratio of tetramethyldihydrodisiloxane to long-chain alkylsilane coupling agent is (0.1-0.5):

1.

10. A method for preparing a bimolecular long-chain alkylsilane gel composition according to any one of claims 1-9, characterized in that, The preparation method includes: (1) Mix the vinyl-terminated polydimethylsiloxane component and the bimolecular long-chain alkylsilane coupling agent evenly; (2) Add thermally conductive filler and mix evenly, then dehydrate under vacuum; (3) Add hydrogen-containing polysiloxane, curing inhibitor and platinum catalyst in sequence, and mix well; (4) Vacuum degassing, and store at -40-0℃ after filling.

Citation Information

Patent Citations

  • Heat-conducting organic silicon composite material for chip packaging and preparation method of heat-conducting organic silicon composite material

    CN117701234A